Borna Disease Virus Nucleoprotein Requires both Nuclear Localization and Export Activities for Viral Nucleocytoplasmic Shuttling - Kobayashi, Takeshi (American Society for Microbiology, 2001)
Nuclear transport of viral nucleic acids is crucial to the life cycle of many viruses. Borna disease virus (BDV) belongs to the order Mononegavirales and replicates its RNA genome in the nucleus. Previous studies have suggested that BDV nucleoprotein (N) and phosphoprotein (P) have important functions in the nuclear import of the viral ribonucleoprotein (RNP) complexes via their nuclear targeting activity. Here, we showed that BDV N has cytoplasmic localization activity, which is mediated by a nuclear export signal (NES) within the sequence. Our analysis using deletion and substitution mutants of N revealed that NES of BDV N consists of a canonical leucine-rich motif and that the nuclear export activity of the protein is mediated through the chromosome region maintenance protein-dependent pathway. Interspecies heterokaryon assay indicated that BDV N shuttles between the nucleus and cytoplasm as a nucleocytoplasmic shuttling protein. Furthermore, interestingly, the NES region overlaps a binding site to the BDV P protein, and nuclear export of a 38-kDa form of BDV N is prevented by coexpression of P. These results suggested that BDV N has two contrary activities, nuclear localization and export activity, and plays a critical role in the nucleocytoplasmic transport of BDV RNP by interaction with other viral proteins.